2020
DOI: 10.1037/dev0000846
|View full text |Cite
|
Sign up to set email alerts
|

Religious testimony in a secular society: Belief in unobservable entities among Chinese parents and their children.

Abstract: When learning about the existence of unobservable scientific phenomena such as germs or religious phenomena such as God, children are receptive to the testimony of other people. Research in Western cultures has shown that by 5 to 6 years of age, children-like adults-are confident about the existence of both scientific and religious phenomena. We examined the beliefs of secular and Christian children growing up in China as well as the beliefs of their parents. All participants-secular and Christian children, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 40 publications
10
43
0
Order By: Relevance
“…This finding held irrespective of religious education and the children justified this with reference to ordinary causal constraints. There is evidence however, that as they continue to mature, a religious upbringing can influence children to treat religious narratives as though they were realistic (Cui, Clegg, Yan, Davoodi, Harris, & Corriveau, 2020;Corriveau, Chen, & Harris, 2014;Vaden & Woolley, 2011;Woolley & Cox, 2007). Notably, this pattern does not emerge for children with a secular upbringing, suggesting that, in the absence of religious socialization, children display a remarkable degree of skepticism (Cui et al, 2020;Chen, & Harris, 2014).…”
Section: The Development Of Atheistic Thinkingmentioning
confidence: 99%
“…This finding held irrespective of religious education and the children justified this with reference to ordinary causal constraints. There is evidence however, that as they continue to mature, a religious upbringing can influence children to treat religious narratives as though they were realistic (Cui, Clegg, Yan, Davoodi, Harris, & Corriveau, 2020;Corriveau, Chen, & Harris, 2014;Vaden & Woolley, 2011;Woolley & Cox, 2007). Notably, this pattern does not emerge for children with a secular upbringing, suggesting that, in the absence of religious socialization, children display a remarkable degree of skepticism (Cui et al, 2020;Chen, & Harris, 2014).…”
Section: The Development Of Atheistic Thinkingmentioning
confidence: 99%
“…For example, US adults and children frequently refer to the causal powers of unobservable scientific and supernatural agents. Despite these crossdomain similarities in patterns of justification, children profess more confidence in the existence of scientific as compared to supernatural unobservables (among other endorsed entities), in most of the cultural contexts studied thus far Cui et al, 2019;Davoodi et al, 2020Davoodi et al, , 2018Guerrero, Enesco, & Harris, 2010;Harris & Corriveau, 2021;. One possible explanation for the differential level of confidence is that there is important linguistic variation in the testimony surrounding each type of entity.…”
mentioning
confidence: 99%
“…Recent studies conducted in Mainland China highlight the importance of the home environment for children's developing beliefs about unobservable phenomena. Cui et al (2019) showed that parents and their children (both 5-to 6-yearolds and 9-to 11-year-olds) who adopted the majority secular view of this culture were skeptical about the existence of religious concepts. By contrast, Christian parents and their children (a minority group in China) were confident that religious entities exist.…”
mentioning
confidence: 99%
See 2 more Smart Citations